Regulation of Polyhydroxybutyrate Synthesis in the Soil Bacterium Bradyrhizobium diazoefficiens - Quelas, Juan Ignacio (2016)
Polyhydroxybutyrate (PHB) is a carbon and energy reserve polymer in various prokaryotic species. We determined that, when grown with mannitol as the sole carbon source, Bradyrhizobium diazoefficiens produces a homopolymer composed only of 3-hydroxybutyrate units (PHB). Conditions of oxygen limitation (such as microoxia, oxic stationary phase and bacteroids inside legume nodules) were permissive for the synthesis of PHB, which was observed as cytoplasmic granules. To study the regulation of PHB synthesis, we generated mutants in the regulator gene phaR and the phasin genes phaP1 and phaP4. Under permissive conditions, mutation of phaR impaired PHB accumulation, and a phaP1/phaP4 double mutant produced more PHB than the wildtype, which was accumulated in a single, large cytoplasmic granule. Moreover, PhaR negatively regulated the expression of phaP1 and phaP4 as well as of phaA1, phaA2 (3-ketoacyl-CoA thiolase), phaC1, phaC2 (PHB synthases), and fixK2 (CRP/FNR-type transcription regulator of genes for microoxic lifestyle). In addition to the depressed PHB cycling, phaR mutants accumulated more extracellular polysaccharide and promoted higher plant shoot dry weight and competitiveness for nodulation than the wildtype, by contrast to phaC1 mutant strains, defective in PHB synthesis. These results suggest that phaR not only regulates PHB granules formation by controlling the expression of phasins and biosynthetic enzymes, but also acts as global regulator of excess carbon allocation and symbiosis by controlling fixK2.